Gamma-ray emission from interactions between jets and BLR clouds - del Palacio, Santiago (2019)
Blazars -active galactic nuclei with a jet pointing towards the observer- are the most numerous -ray sources detected until date. In this work we show preliminary results of a model in which broad-line region (BLR) clouds penetrate in the jet, producing shocks capable of accelerating relativistic electrons; these electrons emit -rays when they interact with the photons coming from the BLR clouds. We calculate semi-analytically the dynamical evolution of a typical cloud inside the jet, the energy distribution of the locally accelerated electrons, and the high-energy emission the latter produce, taking into account relativistic effects. We estimate the duty-cycle of these interactions in order to find whether they occur as discrete events or almost continuous. We compare the observed -ray fluxes with the ones predicted by our model and discuss the implications in terms of particle acceleration efficiency and mass-loading in the blazar jets.